TGF-β signaling in intervertebral disc health and disease. Issue 8 (August 2019) - Chen, S.; Liu, S.; Ma, K.; Zhao, L.; Lin, H.; Shao, Z.
Summary: Objective: This paper aims to provide a comprehensive review of the changing role of transforming growth factor-β (TGF-β) signaling in intervertebral disc (IVD) health and disease. Methods: A comprehensive literature search was performed using PubMed terms 'TGF-β' and 'IVD'. Results: TGF-β signaling is necessary for the development and growth of IVD, and can play a protective role in the restoration of IVD tissues by stimulating matrix synthesis, inhibiting matrix catabolism, inflammatory response and cell loss. However, excessive activation of TGF-β signaling is detrimental to the IVD, and inhibition of the aberrant TGF-β signaling can delay IVD degeneration. Conclusions: Activation of TGF-β signaling has a promising treatment prospect for IVD degeneration, while excessive activation of TGF-β signaling may contribute to the progression of IVD degeneration. Studies aimed at elucidating the changing role of TGF-β signaling in IVD at different pathophysiological stages and its specific molecular mechanisms are needed, and these studies will contribute to safe and effective TGF-β signaling-based treatments for IVD degeneration.